Wpływ działalności górniczej na zmiany rzeźby terenu powiatu bieruńsko-lędzińskiego = The influence of mining activity on the geomorphology of Bieruń-Lędziny district - Gawor, Łukasz; Marcisz, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the study was inventarization, mapping and valorization of coal mining waste dumps coming from the mines functioning in the area of Bieruń-Lędziny district, regarding their influence on the geomorphology. There was done a characterization of dumps of wastes from coal mining, there were presented environmental hazards connected with disposing ofwastes and there was evaluated a state of management of the dumps as well as potential possibilities of recovery of coal from the dumps. Valorization of described objects was done using author`s methodology, concerning questions of reclamation, management, accessibility and environmental hazards. There was also described an influence of anthropogenic landforms on the relief of Bieruń-Lędziny district.
Keywords: zwałowiska pogórnicze; rekultywacja; odzysk węgla z odpadów; coal mining waste dumps; reclamation; recovery of coal